Effectiveness of “Тhe IUCN red list of threatened species” application on a regional scale: current state of the “Red Data books” of Russia - Popov, Igor; Fadeeva, Anastasia; Palenova, Elena; Shamilishvily, George; Gorin, Kirill; Burdo, Andrey; Melchakova, Evgenia; Trofimova, Yulia; Sukristik, Viktor; Morova, Nadezhda; Kroo, Ksenia; Kirillova, Yulia (Biological Communications, 2017)
Nowadays at least 140 Red Data books or lists are used in Russia. They reflect threatened species of various subdivisions of Russia in addition to all-Russian Red Data book. None of them uses criteria for the species assessment of the modern version of the IUCN list. Non-threatened species had not been included in the Russian red books. Most of species listed in the all-Russian Red Data book (77 %) has not yet been assessed for the IUCN red list. These particularities indicate on the necessity of gap-analysis in the planning of the following work on the IUCN red list keeping. It should focus first of all on revealing of the most urgent objectives, but not on the simple increase of species assessments. Now more than a half of species of “Тhe IUCN red list of threatened species” are not threatened ones, that is why its title does not reflect its contents.